The Influence of Social Media on the Development of Indonesian Among Teenagers: New Words and Abbreviations - Khoiri, Abdul Azis (Universitas Syiah Kuala, 2024)
Social media has a significant impact on the development of Indonesian teenagers, especially in terms of adding new words and abbreviations. The aim of this research is to study teenage slang and how it impacts their Indonesian language development. To collect data, qualitative descriptive methods were used in this research, and three teenagers who were active in social media were observed, recorded, and interviewed. Research finds that teenagers prefer to use slang rather than speak good and correct Indonesian. As a result, there will be a worrying impact on the existence of Indonesian language use. Efforts to remember the correct use of Indonesian on social media will help better communication and maintain good language use in accordance with language norms